Reading intensively: What do the students really need? - Dzurriyyatun Ni'mah; Fitri Awaliyatush Sholihah (Universitas Islam Sultan Agung, 2022)
Intensive reading plays a great role in enhancing students’ reading comprehension. Effective teaching materials are the best assistance for students. Often, in intensive reading class, lecturers neglected the students’ needs and preferences regarding the reading texts and topics being discussed. The materials only come from the lecturers’ perspectives. This study explores the students' needs and lecturers' perceptions toward the effective teaching materials of intensive reading. A questionnaire, delivered to 71 English Department students who have completed the Reading 1 course, is used for analysing the students' needs and preferences on intensive reading materials. Moreover, two English lecturers who experienced in teaching intensive reading for five years were interviewed to get detailed information about the students' needs and effective materials on intensive reading. The data were then analysed using a quantitative and descriptive qualitative approach. The result showed that the reading materials which offer various genres and topics, lists of new vocabularies, clear explanations about reading and vocabulary skills, as well as complete exercises to test the reading comprehension were viewed proper for both teachers and students. This research finding gives important information to develop effective reading materials for both sides.